Further studies on the induced haemotological changes in treated insects. - Sharma, V. P. (Contributions to Entomology = Beiträge zur Entomologie, 1966)
Haemotological changes caused by the application of aldrin, allethrin, endrin, nuvan, phosdrin and sevin were studied on adults of Periplaneta americana (Linnaeus), nymphs of Poecilocerus pictus Fabricius, and larvae of Prodenia litura Fabricius. The action of the insecticides on the insects produced various types of abnormalities that were not specific to the insecticides. The changes observed were of the same type as reported by Chattoraj & Sharma (1965). It was observed that only slight haemotological changes were caused by the application of aldrin and nuvan; marked changes were caused by the application of phosdrin and endrin; and intense haemotological changes resulted from the application of sevin and allethrin.